Non‐specific and specific DNA binding modes of bacterial histone, HU, separately regulate distinct physiological processes through different mechanisms. Issue 4 (20th February 2023) - Verma, Subhash C.; Harned, Adam; Narayan, Kedar; Adhya, Sankar
Abstract: The histone‐like protein HU plays a diverse role in bacterial physiology from the maintenance of chromosome structure to the regulation of gene transcription. HU binds DNA in a sequence‐non‐specific manner via two distinct binding modes: (i) random binding to any DNA through ionic bonds between surface‐exposed lysine residues (K3, K18, and K83) and phosphate backbone (non‐specific); (ii) preferential binding to contorted DNA of given structures containing a pair of kinks (structure‐specific) through conserved proline residues (P63) that induce and/or stabilize the kinks. First, we show here that the P63‐mediated structure‐specific binding also requires the three lysine residues, which are needed for a non‐specific binding. Second, we demonstrate that substituting P63 to alanine in HU had no impact on non‐specific binding but caused differential transcription of diverse genes previously shown to be regulated by HU, such as those associated with the organonitrogen compound biosynthetic process, galactose metabolism, ribosome biogenesis, and cell adhesion. The structure‐specific binding also helps create DNA supercoiling, which, in turn, may influence directly or indirectly the transcription of other genes. Our previous and current studies show that non‐specific and structure‐specific HU binding appear to have separate functions‐ nucleoid architecture and transcription regulation‐ which may be true in other DNA‐binding proteins. Abstract : HU, the only evolutionarily conserved histone‐like protein in bacteria, exhibits a non‐specific or random binding mode that allows it to bind any duplex DNA without inducing bends and a DNA‐structure‐specific binding mode that stabilizes or induces bends in DNA. This study shows that non‐specific and specific binding modes have separate functions‐chromosome organization and transcription regulation, which may be true in other architectural DNA‐binding proteins.